Martin Luther's Reformation and Its Impact on Modernization - Daniel Ling LI, (Journal of Research for Christianity in China (JRCC), 2025)
This year marks the 500th anniversary of the Protestant Reformation initiated by Martin Luther. I too wish to explore why this Reformation exerted such profound influence on the course of world history. While countless works have already examined the Reformation's impact on modernization, I do not presume to offer any particularly novel insights. Instead, I aim to examine its influence on modern thought through several key concepts. The society we inhabit is undergoing rapid and constant transformation, with its direction and objectives seemingly well-defined: the modernization of both nation and society. Thus, this topic retains considerable contemporary relevance.